2021
DOI: 10.1167/tvst.10.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Relating Retinal Vascular Oxygen Saturation and Microvasculature Morphology at Progressive Stages of Diabetic Retinopathy

Abstract: Purpose Diabetic retinopathy (DR) is a common cause of vision loss in working age adults and presents changes in retinal vessel oxygenation and morphology. The purpose of this study was to test the hypothesis that there is an association of retinal vessel oxygen saturation with vessel density (VD) and tortuosity in DR. Methods Ninety-five subjects were classified in the following groups: nondiabetic control ( N = 25), no DR ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previously, most studies have used SO 2 to indirectly observe abnormal oxygen metabolism in DM. In our study, we found SO 2 A and SO 2 V increase gradually, and SO 2 A_V increases first and then decreases with the development of DM, which is consistent with previous studies [8,11,12,31]. There are several reasons to explain SO 2 change in DM, including the thickening of vessel walls to decrease oxygen diffusion, high levels of HbA1c to retain the oxygen in the vessel, blood shunting and bypassing of nonperfused areas [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, most studies have used SO 2 to indirectly observe abnormal oxygen metabolism in DM. In our study, we found SO 2 A and SO 2 V increase gradually, and SO 2 A_V increases first and then decreases with the development of DM, which is consistent with previous studies [8,11,12,31]. There are several reasons to explain SO 2 change in DM, including the thickening of vessel walls to decrease oxygen diffusion, high levels of HbA1c to retain the oxygen in the vessel, blood shunting and bypassing of nonperfused areas [32].…”
Section: Discussionsupporting
confidence: 91%
“…However, literature findings on retinal SO 2 between DM without DR (NDR) and NPDR were inconsistent. Compared to NDR, some studies demonstrated significantly increased venular SO 2 in NPDR [8,9], while other studies found no significant change in retinal SO 2 [10][11][12]. Nevertheless, it should be noted that it is not comprehensive to evaluate SO 2 alone since it only indicates the percentages of oxyhemoglobin in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…OCTA, a novel noninvasive technique, was recently adopted to quantitatively measure retinal and choroidal microvasculature in different ocular and systemic diseases, such as glaucoma (27,28), age-related macular degeneration (29-31), optic neuropathies (32-35), leukemia (36), diabetic retinopathy (37)(38)(39)(40), and TAO (14,19,20,41,42), and to evaluate the severity and prognosis of these diseases. Our study showed that the macular retinal VD was significantly decreased in the ODE and NODE groups compared with the normal group.…”
Section: Discussionmentioning
confidence: 99%